Basic manufacturing / Roger Timings and Mike Tooley ; edited by Trevor Thompson. - Timings, R. L. (Roger Leslie), 1927- (Newnes, 2001)
This volume provides a comprehensive and readable introduction to the technical and business aspects of the manufacturing industry.